Dual stimuli-responsive hydrogels for colon targeted drug delivery - Mohmmad Imad Rabeh; Matthew Wylie; Colin P McCoy (University of Huddersfield Press, 2022)
Colon targeted drug delivery systems are promising for the treatment of local diseases. The colon possesses a diverse microbiome that secretes a number of biomolecules, such as enzymes, that can be exploited for targeted drug delivery. Here, we report the synthesis of 2-hydroxyethyl methacrylate and methacrylic acid copolymer hydrogels crosslinked with an enzyme-sensitive crosslinking agent. The swelling and drug release properties of hydrogels were observed in pH 1.2, pH 6.5 and pH 7.4, and in the presence of rat cecal content. Swelling studies revealed pH responsivity of the hydrogels while the release kinetics of metronidazole from hydrogels containing an enzyme-labile crosslinker were faster in the presence of rat cecal content. The results show that dual responsive hydrogels could provide a promising platform for colonic drug delivery